Respirar utopias e as corporeidades: estudo sobre discursos cênicos de artistas negras na cidade de São Paulo - Coelho, Daiana de Moura Bernardes (2024)
Black women artists tell stories that are not found in textbooks. They evoke and connect memories through the sharing of experiences of the Black body. Artworks that hold fundamental importance for the creation of networks of ethical, aesthetic, sensitive, poetic, and political resistances, which critically contribute to the education and understanding of contemporary Brazilian society. The thesis is organized into three sections, named Utopias D'água (Water Utopias, Breathing, and Cenovivências). Notebooks that reflect the experience of an interdisciplinary research that dances at the interface between education and performing arts studies. The theoretical-methodological foundations are gender studies, Black and post-colonial feminist studies, with an intersectional approach. Viandança is the forge, the methodology I create to organize the choreographies of the process and dialogue with the works of Black artists (before, during the COVID-19 pandemic, and in the post-vaccine period). The creation of this methodology was necessary to analyze, breathe, and converse with artistic works perceived as seedlings of utopias at the crossroads of the São Paulo scene. Broadly speaking, in conjunction with the historical context, with the pulse of the city, and inspired by theories of intellectuals such as Conceição Evaristo, Beatriz Nascimento, and Lélia Gonzalez, I call these creations by Black women "cenovivências". The methodological procedures aimed at the enjoyment through the co-living experiences are: bibliographical review, records of encounters with artists, works, and territories in field notebooks, analysis of shows, and creation of geolocation maps (Google MyMaps). The production of these discourses in performing arts and the construction of subjectivities that 'contradict statistics' form counter-currents, advocated here as artivisms, a resurgence and updating of quilombos in the city of São Paulo. Believing in powerful relationships, connections, and alliances to dream of new Afro-futures, these Utopias D'água Notebooks I, II and III are part of an immense chorus of Afro-diasporic and Afro-pindoramic discourses spread throughout the world that come together like whale songs, through the body. Establishing communication patterns that keep our internal waters balanced. Speeches that come from the viscera. Insurgent cries. Songs, words, letters, water gestures cascading tides on the asphalt in the metropolis.